PENTINGNYA PENGAWASAN PARTISIPATIF DALAM HAL MENANGKAL HOAX DI MEDIA SOSIAL SEBAGAI PROSES MENGAWAL PEMILU SERENTAK DI INDONESIA - Yosua Christian Lumban Tobing (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
In today's digital era, social media is now the main source of information for many people. However, the spread of hoaxes and fake news is increasingly prevalent and has the potential to damage the fabric of society. According to Linda Walsh's book Sins Against Science, the term “fake news” or “disinformation” was coined in English after the industrial revolution. It is believed to have first started in 1808(Mughniy Arnita, 2024). The word “hocus” from the spell “hocus pocus” is thought to have been the source of the word “hocus” for hundreds of years. A simile-like phrase often used by magicians. The Latin phrase “hoc est corpus” which translates to “this is the body,” is the source of the English word “hoax”. Magicians usually use this word to assert the truth of something that may not always be the case. The English word for “hoax” itself means “fake news”. Hoaxes related to elections are often used, but Bawaslu, an organization required by law to oversee the implementation of elections, has an opportunity to improve the quality of elections that are directly related to the quality of democracy through the Participatory Monitoring program. The active involvement of the community, which is one of the important elements in elections, needs to be strengthened as an effort to ensure the quality of elections held is getting better both from a procedural and substantive point of view. One of the key tactics to stop hoaxes on social media during general elections is participatory monitoring. The General Election Supervisory Agency (Bawaslu) has undertaken a number of initiatives to improve participatory monitoring, particularly in response to the growing danger of hoaxes in the digital era. In this journal, the author will discuss the elements of participatory monitoring, strategies in preventing hoaxes on social media, and Bawaslu's efforts in preventing, intervening and providing community-based prevention techniques.